Clinical Practice Guideline: Bell's Palsy. (4th November 2013) - Baugh, Reginald F.; Basura, Gregory J.; Ishii, Lisa E.; Schwartz, Seth R.; Drumheller, Caitlin Murray; Burkholder, Rebecca; Deckard, Nathan A.; Dawson, Cindy; Driscoll, Colin; Gillespie, M. Boyd; Gurgel, Richard K.; Halperin, John; et al.
Abstract : Objective: Bell's palsy, named after the Scottish anatomist, Sir Charles Bell, is the most common acute mono‐neuropathy, or disorder affecting a single nerve, and is the most common diagnosis associated with facial nerve weakness/paralysis. Bell's palsy is a rapid unilateral facial nerve paresis (weakness) or paralysis (complete loss of movement) of unknown cause. The condition leads to the partial or complete inability to voluntarily move facial muscles on the affected side of the face. Although typically self‐limited, the facial paresis/paralysis that occurs in Bell's palsy may cause significant temporary oral incompetence and an inability to close the eyelid, leading to potential eye injury. Additional long‐term poor outcomes do occur and can be devastating to the patient. Treatments are generally designed to improve facial function and facilitate recovery. There are myriad treatment options for Bell's palsy, and some controversy exists regarding the effectiveness of several of these options, and there are consequent variations in care. In addition, numerous diagnostic tests available are used in the evaluation of patients with Bell's palsy. Many of these tests are of questionable benefit in Bell's palsy. Furthermore, while patients with Bell's palsy enter the health care system with facial paresis/paralysis as a primary complaint, not all patients with facial paresis/paralysis have Bell's palsy. It is a concern that patients with alternative underlying etiologies may be misdiagnosed or have unnecessary delay in diagnosis. All of these quality concerns provide an important opportunity for improvement in the diagnosis and management of patients with Bell's palsy. Purpose: The primary purpose of this guideline is to improve the accuracy of diagnosis for Bell's palsy, to improve the quality of care and outcomes for patients with Bell's palsy, and to decrease harmful variations in the evaluation and management of Bell's palsy. This guideline addresses these needs by encouraging accurate and efficient diagnosis and treatment and, when applicable, facilitating patient follow‐up to address the management of long‐term sequelae or evaluation of new or worsening symptoms not indicative of Bell's palsy. The guideline is intended for all clinicians in any setting who are likely to diagnose and manage patients with Bell's palsy. The target population is inclusive of both adults and children presenting with Bell's palsy. Action Statements: The development group made a strong recommendation that (a) clinicians should assess the patient using history and physical examination to exclude identifiable causes of facial paresis or paralysis in patients presenting with acute‐onset unilateral facial paresis or paralysis, (b) clinicians should prescribe oral steroids within 72 hours of symptom onset for Bell's palsy patients 16 years and older, (c) clinicians should not prescribe oral antiviral therapy alone for patients with new‐onset Bell's palsy, and (d) clinicians should implement eye protection for Bell's palsy patients with impaired eye closure. The panel made recommendations that (a) clinicians should not obtain routine laboratory testing in patients with new‐onset Bell's palsy, (b) clinicians should not routinely perform diagnostic imaging for patients with new‐onset Bell's palsy, (c) clinicians should not perform electrodiagnostic testing in Bell's palsy patients with incomplete facial paralysis, and (d) clinicians should reassess or refer to a facial nerve specialist those Bell's palsy patients with (1) new or worsening neurologic findings at any point, (2) ocular symptoms developing at any point, or (3) incomplete facial recovery 3 months after initial symptom onset. The development group provided the following options : (a) clinicians may offer oral antiviral therapy in addition to oral steroids within 72 hours of symptom onset for patients with Bell's palsy, and (b) clinicians may offer electrodiagnostic testing to Bell's palsy patients with complete facial paralysis. The development group offered the following no recommendations : (a) no recommendation can be made regarding surgical decompression for patients with Bell's palsy, (b) no recommendation can be made regarding the effect of acupuncture in patients with Bell's palsy, and (c) no recommendation can be made regarding the effect of physical therapy in patients with Bell's palsy.